Gamification in science: game platforms for learning - Sotnik, S. V.; Andreiev, А. S. (My University, 2023)
The thesis deals with application of game platforms for playing games in academic disciplines in higher education institutions with technical bias. A detailed analysis of Kahoot! and Quizlet is carried out. This work analyzed well-known game platforms Kahoot! and Quizlet for gamerization in higher education institutions. Work algorithms in each platform and extensive comparative analysis are given. As result, it is determined that Kahoot! and Quizlet are two popular online services for teaching and learning games. They have different features and functions that can be useful in different educational contexts. Quizlet specializes in learning cards and word sets – convenient platform for learning new vocabulary and terms. Kahoot! allows you to create interactive quizzes and polls, with addition of audio, video, text files and there are also variety of game modes such as "Classic", "Voting" and "Group Mode".
Keywords: gamification; science; game; science